A Computational Approach for Molecular Characterization of Covaxin (BBV152) and Its Ingredients for Assessing Its Efficacy against COVID-19 - Atala B. Jena; Asim K. Duttaroy (MDPI AG, 2022)
SARS-CoV-2 vaccination is a life-saving strategy for the entire population living in this pandemic. Several vaccines were developed using different platforms such as nucleic acids, viral vectors recombinant proteins, live attenuated, and inactivated virus modalities, etc. Although immunogenicity and efficacy of these COVID vaccines were investigated, Covaxin (a vaccine code-named BBV152), an inactivated COVID-19 vaccine, has not been well studied yet. This study aimed to explore the interactions between biomolecules with vaccine adjuvants by analyzing molecular and protein-protein interactions of S protein, angiotensin-converting enzyme 2 (ACE2), and human serum albumin (HSA) with the ingredients of Covaxin (2-phenoxyethanol and imidazoquinolinone) by computational methods using Autodock Vina, Cluspro, and Swiss ADME. In addition, its drug-likeness property was investigated. The binding energies using Autodock Vina showed stronger interactions of 2-phenoxyethanol and imidazoquinolinone with viral surface protein, S protein, human cell membrane receptor ACE2, and drug carrier plasma HSA (−5.2, −5.3 and −5.3 kcal/mol; −8.5, −8.5 and −9.1 kcal/mol, respectively). The interaction between S protein with ACE2 in the presence of 2-phenoxyethanol and imidazoquinolinone hindered the S protein function by reducing the binding energy between these proteins. In addition, imidazoquinolinone may have the drug-likeness property based on pharmacokinetic and physicochemical parameters. These results suggest that the Covaxin vaccine, owing to these ingredients, may impart greater efficacy in averting the virus and thus it may be more effective in producing herd immunity. In conclusion, for the first time, this computational study predicts the possible useful effects of these two adjuvants of Covaxin in therapeutic and drug-likeness strategies against SARS-CoV-2.